The global auction : the broken promises of education, jobs, and incomes - Brown, Phillip, 1957-; Lauder, Hugh, 1948-; Ashton, D. N. (New York ; Oxford : Oxford University Press, 2011)
For decades, the idea that more education will lead to greater individual and national prosperity has been a cornerstone of developed economies. Challenging this conventional wisdom, 'The Global Auction' forces us to reconsider our deeply held and mistaken views about how the global economy really works and how to thrive in it.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Social mobility -- United States; Educational attainment -- United States; Labor market -- United States; American Dream